2007
DOI: 10.1111/j.1462-5822.2006.00825.x
|View full text |Cite
|
Sign up to set email alerts
|

Virulence of Porphyromonas gingivalis is altered by substitution of fimbria gene with different genotype

Abstract: SummaryPorphyromonas gingivalis is a periodontal pathogen whose fimbriae are classified into six genotypes based on the diversity of the fimA genes encoding each fimbria subunit. It was suggested that P. gingivalis strains with type II fimbriae were more virulent than type I strains. For the present study, we generated the mutants in which fimA was substituted with different genotypes to study virulence of type II fimbriae. Using plasmid vectors, fimA of ATCC33277 (type I strain) was substituted with type II f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
114
1
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(128 citation statements)
references
References 53 publications
(81 reference statements)
7
114
1
5
Order By: Relevance
“…Because fimA-disrupted mutants have been shown to lose almost all of their invasive ability, 26 we analyzed the entire coding sequence of the fimA gene to determine an underlying mechanism for the heterogenic invasive ability of P. gingivalis. A sequence similarity search revealed that KUMC-P10 has a type I genotype, while all the other strains have type II.…”
Section: Resultsmentioning
confidence: 99%
“…Because fimA-disrupted mutants have been shown to lose almost all of their invasive ability, 26 we analyzed the entire coding sequence of the fimA gene to determine an underlying mechanism for the heterogenic invasive ability of P. gingivalis. A sequence similarity search revealed that KUMC-P10 has a type I genotype, while all the other strains have type II.…”
Section: Resultsmentioning
confidence: 99%
“…Cell Culture Immortalized HGE cells 15) were kindly provided by Professor Murakami (Osaka University Graduate School of Dentistry). HGE cells were grown in Humedia KB-2 (Kurabo, Osaka, Japan) at 37°C with 5% CO 2 as described previously, 15) and 24 h before stimulation of P. gingivalis vesicles, the cells were moved to Dulbecco's modified Eagle's medium (Sigma, St. Louis, MO, U.S.A.) with 10% fetal calf serum (Invitrogen Co., Carlsbad, CA, U.S.A.).…”
Section: Methodsmentioning
confidence: 99%
“…When the type I allele was replaced with the type III or IV allele, increased invasion of gingival fibroblasts were seen compared to that achieved with the isogenic parent strain. By using plasmid vectors, Kato et al [26] substituted fim A of ATCC 33277 with type II fim A, and that of OMZ314 (type II strain) with type I fim A. Replacement of type I fim A with type II increased bacterial adhesion/invasion to epithelial cells, whereas substitution with type I fim A resulted in reduced efficiency.…”
Section: Introductionmentioning
confidence: 99%